Warm-ups for Musicians: Systematized and Terminology Reviews - Fleet, Emma (Université d'Ottawa / University of Ottawa, 2021)
Context: Many musicians experience playing-related pain and injuries. One of the recommended injury prevention strategies is to warm-up prior to playing a musical instrument. However, this recommendation is not always supported with empirical data. Additionally, multiple terms are used to describe warm-ups and may differ between authors, creating confusion around this injury prevention strategy. Objectives: The objectives of this thesis are to search for evidence-based studies that would support the benefit of warm-ups for musicians, reduce the confusion around musicians’ warm-ups, and bring clarity to the definition of warm-up. Methodology: In order to do so, this thesis presents two studies. The first study consisted of doing a systematized review of English published articles in order to identify if there was evidence to support the statement that warm-ups prevent injury. The methodology and results of each included article were evaluated using the American Academy for Cerebral Palsy and Developmental Medicine (AACPDM)’s levels of evidence. The second article consisted of a terminology review and taxonomy in order to identify terms, organize them into categories and define warm-ups. The corpus contained the same articles that were included in the systematized review. Terms were identified from the corpus and the most frequently mentioned terms were used for the definition of warm-up. Terms were also categorized in a taxonomy in order to illustrate the different types of warm-ups that are recommended to musicians. Results: Twenty-nine studies were included in the analysis of the systematic review. Of these 29 studies, only one ranked at level I, which is the highest level of evidence, and most studies ranked at level V. The one study that was ranked at level I indicated that all three tested warm-up conditions did not have a muscular effect. Therefore, at the moment, there seems to be no evidence that supports the statement that warm-ups prevent injury. The terminology review led to the following definition of warm-up: “A routine, habit or exercise(s) that is/ are completed prior to playing repertoire or learning new material on a music instrument in order to prepare physically and mentally the musician. The following can be included as part of a musician’s warm-up: physical warm-up (completed without the instrument, for example stretches), musical warm-up (completed with the instrument, for example: scales, familiar tune/ favorite tune, long tones), and psychological warm-up.” It was also determined that stretching should also be defined as it is not always perceived as a warm-up. Stretching was defined as “Slow, controlled and progressive movements that are maintained for at least 20-30 seconds. These are done at various intervals throughout the day such as prior, during (breaks), and after the practice of a music instrument. They are referred to as physical exercises (away from the instrument). The following are some examples of stretching exercises: wrist rotations, forward neck roll, oppositional finger-wrist press, hand-finger extensions, fist clench and unclench, arms-bicep curls, handshakes, arms-triceps extension, and fingers clenched and unclenched.” The taxonomy indicated three warm-up categories: physical, musical and psychological. The physical and musical warm-ups were then subcategorized. It was not possible to subcategorize psychological warm-ups due to a lack of definition and examples in the literature. This study was a first step towards standardization, but further research is necessary in order to standardize a methodology and protocol.
Keywords: warm-up; stretching; musicians; music; injury prevention